Official Plans for Dealing with the Possible Outbreak of Monkeypox in Iran (First detected case in the southwestern Iranian city of Ahvaz) - Jamie Cone; Solmaz Sadat Hosseini Zijoud (Novelty in Clinical Medicine, 2022)
Letter to the Editor